Prevalence of ABO, Rh (D, C, c, E, and e), and Kell (K) antigens in blood donors: A single-center study from South India - Banerjee Soumee; A. M. Shanthala Devi; Subramanian Sitalakshmi (Asian Journal of Transfusion Science)
BACKGROUND: Although ABO and RhD are the clinically significant blood group antigens that are routinely tested for, other blood group antigens may become important in multiply transfused patients due to risk of alloimmunization. Knowledge of antigen prevalence in a population is important in the context of alloimmunization and antigen matching. This study aims to do the same in a population of voluntary blood donors of a center in South India. AIMS AND OBJECTIVES: To study the ABO, Rh (D, C, c, E, and e), and Kell (K) antigen and Rh phenotype prevalence in whole blood donors donating at the blood bank of a tertiary care hospital in South India. MATERIALS AND METHODS: One thousand and two hundred eligible whole blood donors were chosen by random sampling between November 2017 and April 2019. After administration of informed consent and routine testing for ABO grouping, RhD typing, and indirect antiglobulin test, Rh and Kell typing was done on appropriate gelcards and the data were analyzed to arrive at phenotypes. RESULTS: 97.6% of the donors were male and 2.4% were female. They were divided into 7 different categories based on the regions of origin: Kerala, Andhra Pradesh, Tamil Nadu, Karnataka, West Bengal, North India, and others with the largest number of donors hailing from Karnataka (38.5%). The ABO distribution, in descending order, was as follows: O (38%), B (34.5%), A (20.6%), and AB (6.8%). The prevalence of the Rh antigens was as follows: D: 93.4%, C: 87.9%, c: 55.6%, E: 19.3%, and e: 98.8%. K was present in 1.4% of the population. Since genotyping has not been done, the most common “presumed” Rh phenotype among RhD-positive donors was R1R1 (46.4% of total donors and 49.5% of RhD-positive donors). The most common phenotype among RhD-negative donors was rr (5.9% of total donors and 92.2% of RhD-negative donors). The order of prevalence of the ABO, Rh, and K antigens and the Rh phenotypes remained the same irrespective of gender, ABO group, and region of origin. CONCLUSION: This population-based study analyzes a donor population as a whole and separately as per regions of origin and shows that antigen prevalence and thereby risk of alloimmunization does not vary markedly among the different population subsections. Hence, even where extended phenotyping and antigen matching cannot be done, risk of alloimmunization may be low. Limiting antigen matching to specific patient subsets like in multiply transfused patients with uncommon phenotypes may, therefore, be an efficient and cost-effective approach.